Tecido urbano actual: continuidade ou descontinuidade? - Paula Guerra (1993)
The reconstruction inherent to the current urban scene configures two basic aspects: the spatial and social. Thus, in this research, we focus on the processes of social and spatial recomposition that have the background and critical process, the area of urban housing, particularly housing social. The complexity inherent in the analysis of this social phenomenon severely limits the claim to exhaust. For now, all the possible analytical strands around a sociological approach to those social processes and dimensions that incorporates. As a process of continuous transformation, the urban and social recomposition - the object of our analytic interest - lining up at the present time, some key dimensions. The first of dimensions/axes of analysis of social recomposition of the urban space focuses on the accelerated fragmentation of urban social forms. This corresponds to the emergence of trends increasingly segregated in the structuring of urban space leading to the existence of a city spatially slashed and with a lacks of social cohesion. Many authors respond to this fragmentation, with the emergence of a "archipelago society", a sort of metaphor for a space marked by a discontinuous order even isolated when compared to the others, contradicting the principles which existed at the genesis of the city, that is, place of exchanges, meetings, multiple crossings.